2020
DOI: 10.3389/fonc.2020.533282
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characterization of Mismatch Repair Gene-Deficient Metastatic Castration-Resistant Prostate Cancer

Abstract: Mismatch repair-deficient (dMMR) prostate cancer is rare and has not been well studied. We aimed to evaluate the clinical characterization of dMMR metastatic castrationresistant prostate cancer (mCRPC) patients. The MMR genes include MLH1, MLH3, MSH2, MSH6, PMS1, PMS2, and EPCAM, and were analyzed by targeted sequencing of plasma cell-free DNA samples. A total of 109 mCRPC patients were identified, including 50 patients with MMR alterations (pathogenic alterations, n = 7; alterations of unknown significance, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In prior series, MMR-deficient prostate cancer has been associated with high-grade histology (grade groups 4-5) and advanced pathological stage, consistent with the aggressive clinical behaviour and short progression-free survival periods observed in these patients. 15,30,31 Ductal histology, 17 tumourinfiltrating lymphocytes 16 and pleomorphic giant tumour cells 27 have also been reported in MMRdeficient prostate cancer. In the present study, MMRdeficient prostate cancers without prior systemic treatment were invariably high-grade.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In prior series, MMR-deficient prostate cancer has been associated with high-grade histology (grade groups 4-5) and advanced pathological stage, consistent with the aggressive clinical behaviour and short progression-free survival periods observed in these patients. 15,30,31 Ductal histology, 17 tumourinfiltrating lymphocytes 16 and pleomorphic giant tumour cells 27 have also been reported in MMRdeficient prostate cancer. In the present study, MMRdeficient prostate cancers without prior systemic treatment were invariably high-grade.…”
Section: Discussionmentioning
confidence: 96%
“…This study has limitations that need to be highlighted. First, the number of cases is relatively small, albeit comparable to prior series of MMR‐deficient prostate cancer 9,15,30,31 . Secondly, because most cases were identified in a sequencing database, a selection bias resulting in enrichment for high‐grade tumours is likely.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…While only a single hypermutagenic polymerase mutation has been reported in CRPC to our knowledge, both dMMR and APOBEC signatures appear in CRPC, but occur infrequently compared to some other cancer types [ 71 , 72 , 73 ]. MSI-high/dMMR tumors were identified in some CRPC cohorts, constituting up to 5% of analyzed patients depending on the cohort analyzed [ 74 , 75 ]. Numerous prostate cancer samples exhibit APOBEC signature mutations that increase along the spectrum of disease progression from localized to mCRPC, although the overall frequency is low compared to several other tumor types [ 71 , 76 ].…”
Section: The Dna Damage Response In Prostate Cancermentioning
confidence: 99%
“…The risk of PCa in men with MMR gene mutations has been demonstrated to be significantly enhanced ( Rantapero et al, 2020 ). Individuals that have MMR mutations are typically predicted to account for 2%–5% of PCa cases ( Ritch et al, 2020 ; Ye et al, 2020 ), and they are generally identified by their Gleason score 8 and de novo metastases ( Dominguez-Valentin et al, 2016 ; Ye et al, 2020 ; Jiang et al, 2021 ; Graham and Schweizer, 2022 ). The genetic mutations in MMR genes in the prostate may aid in understanding PCa carcinogenesis, which may have additional repercussions for ICBs and other types of treatment.…”
Section: Challenges and Controversies In The Management Of Prostate C...mentioning
confidence: 99%